Strong convergence of robust equivariant nonparametric functional regression estimators - Boente Boente, Graciela Lina (2015)
Robust nonparametric equivariant M-estimators for the regression function have been extensively studied when the covariates are in R k . In this paper, we derive strong uniform convergence rates for kernel-based robust equivariant M-regression estimator when the covariates are functional.